Enhancement of the medial olivocochlear system prevents hidden hearing loss - Boero, Luis Ezequiel (2018)
Cochlear synaptopathy produced by exposure to noise levels that cause only transient auditory threshold elevations is a condition that affects many people and is believed to contribute to poor speech discrimination in noisy environments. These functional deficits in hearing, without changes in sensitivity, have been called hidden hearing loss (HHL). It has been proposed that activity of the medial olivocochlear (MOC) system can ameliorate acoustic trauma effects. Here we explore the role of the MOC system in HHL by comparing the performance of two different mouse models: an α9 nicotinic receptor subunit knock-out (KO; Chrna9 KO), which lacks cholinergic transmission between efferent neurons and hair cells; and a gain-of-function knock-in (KI; Chrna9L9′T KI) carrying an α9 point mutation that leads to enhanced cholinergic activity. Animals of either sex were exposed to sound pressure levels that in wild-type produced transient cochlear threshold shifts and a decrease in neural response amplitudes, together with the loss of ribbon synapses, which is indicative of cochlear synaptopathy. Moreover, a reduction in the number of efferent contacts to outer hair cells was observed. In Chrna9 KO ears, noise exposure produced permanent auditory threshold elevations together with cochlear synaptopathy. In contrast, the Chrna9L9′T KI was completely resistant to the same acoustic exposure protocol. These results show a positive correlation between the degree of HHL prevention and the level of cholinergic activity. Notably, enhancement of the MOC feedback promoted new afferent synapse formation, suggesting that it can trigger cellular and molecular mechanisms to protect and/or repair the inner ear sensory epithelium.